Estimation of Energy Potential from Organic Fractions of Municipal Solid Waste by Using Empirical Models at Hyderabad, Pakistan. - Muhammad Safar Korai (Mehran University Research Journal of Engineering and Technology, 2016)
MSW (Municipal Solid Waste) now-a-day is considered as a precious renewable energy resource for various purposes. In view of above fact, one hundred samples of MSW were collected from different locations of study area. Quantities of each organic waste component were determined by using physical balance and also their proximate analysis was performed by using oven and muffle furnace. In this study, nine empirical models were used for estimating the energy value in terms of heat from OFMSW (Organic Fractions of Municipal Solid Waste), namely two of them were based upon physical composition, four of them were on the basis of its proximate analysis and remaining three of them was according to ultimate analysis of OFMSW. From comparison of all energy models, the empirical Model No. 3 and No. 4 based upon proximate analysis have highest energy recovery potential than all of others. Moreover, the result of Model No.3 on the basis of proximate analysis is closer to the calorific value of mixed OFMSW than the values obtained by rest of models. Therefore, this is the best model to be used. From the outcomes of this study it can be realized that the energy recovery from the OFMSW plays a vital role for economical growth of the country. On that account, a systematic approach should be performed in detail before making a decision on such option